Space Treatment in the Ceramic Sculpture of the Potter "Shinyar Abdua – Allah" (Al-Academy, 2016)
Space is considered as an important element in constructing artwork, it can be a dominant and fulfilled part that adds new existence to the content. Each artwork must have a space artistically or analytically. The internal and eternal space of artwork have associated with each other in order to be ann important connected unit that establishes the work epressions and helps the audience to understand it. Such kind of works can be represented by the works of the potter (Sheinyor Abdu Allah) which have uarious expressions of space which this study is based on.The study aims at finding out the treatment of apace in the ceramic sculpture works of the potter (Sheinyar Abdu Allah).The second chapter has many sections. The first section deals with the concept of space philosophically and aesthetically. While the second section focuses o the historical background of the concept of space in Ancient arts, Islamic art, and modern art. The third chapter deals with the procedures like the choice of sample that contains four selected artwork of the potter that illustrate the application of space.The fourth chapter has the following results:-1-The works of (Sheinyar Abud Allah) have a significance of open and flat space with the existence of variety in height, form, and technique which create further space besides the spatial vision that is found through color, texture, the use of material and the creation of visual balance and movable action.2-The space in the potter's works have colored and formative interaction that gives the audience a type of psychological and cognitive embracement.The study has drawn the following conclusion:-1-The space in (Sheinyar Abdu Allah) works has different concepts according to the nature of formation & sculptural structure and the way of treating the space in special quality of using color and composition. He is able to create movable space that can be continuous sometimes through the use of brush and some gazes to present the formative and aesthetic value of space with the aid of special techniques and mixture of unit and color to create definite balance